Analisis Strategi Pembelajaran dalam Meningkatkan Motivasi Belajar Mahasiswa pada Mahasiswa PGMI UINFAS Bengkulu - Fenti Yurni; Rika Andriyani; Nova Asvio; Dalima Septiria; Intan Utami (MODELING: Jurnal Program Studi PGMI, 2024)
The quality of learning in higher education is strongly influenced by students' learning motivation, particularly in teacher education programs such as PGMI (Pendidikan Guru Madrasah Ibtidaiyah). This literature review examines various learning strategies implemented to enhance student motivation among PGMI students at UINFAS Bengkulu. The analysis covers active learning strategies, cooperative learning, self-regulated learning, and technology-integrated instruction. The reviewed studies indicate that active and cooperative learning strategies significantly improve student engagement, intrinsic motivation, and academic performance. Self-regulated learning approaches support students in developing autonomy and metacognitive skills, while technology-based strategies address the digital learning preferences of contemporary students. However, challenges remain, including limited digital literacy among educators, inadequate infrastructure, and the need for pedagogical alignment. The review concludes that a combination of active, cooperative, and technology-supported learning strategies is essential to foster sustainable motivation among PGMI students, provided that institutional support and teacher competence are continuously strengthened.